Sedentary behavior and cardiovascular disease risk: An evolutionary perspective - Higgins, Simon; Pomeroy, Alexander; Bates, Lauren C.; Paterson, Craig; Barone Gibbs, Bethany; Pontzer, Herman; Stoner, Lee (Frontiers in Physiology, 2022)
A ubiquitous aspect of contemporary societies is sedentary behavior (SB), defined as low intensity activities in a seated, reclined, or supine posture. Leading public health agencies, including the World Health Organization, have recognized the strong association between SB and poor health outcomes, particularly cardiovascular disease. However, while public health agencies have begun to advocate for “reductions” in SB, the current US guidelines are typically vague and non-specific. There is good reasoning behind this non-committal advocacy - there is limited mechanistic and clinical evidence to support policy development. To guide SB policy development, it is important to first consider the origins and evolution of SB, including the following: (i) is SB really a novel/contemporary behavior? i.e., how has this behavior evolved? (ii) how did our ancestors sit and in what contexts? (iii) how does SB interact with 24-hour activity behaviors, including physical activity and sleep? (iv) what other historical and contemporary facets of life interact with SB? and (v) in what context do these behaviors occur and how might they provide different evolutionarily novel stressors? This perspective article will synthesize the available evidence that addresses these questions and stimulate discussion pertaining to the lessons that we can learn from an historical and evolutionary perspective. Last, it will outline the gaps in current SB interruption literature that are hindering development of feasible SB reduction policy.